The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1055/s-2000-7473
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evidence for an Extended Tribe ‐ Coccocypseleae (Rubiaceae‐Rubioideae)

Abstract: Coccocypselum is a small neotropical genus of creeping herbs belonging to the Rubiaceae (Rubioideae). A recent macromolecular study suggested a previously unknown relationship between Coccocypselum and two other neotropical genera, Declieuxia and Hindsia, but the morphological evidence for this relationship was obscure. In the present paper, morphological characters supporting the conclusions from macromolecular data are presented. The most important similarities between Coccocypselum, Declieuxia, and Hindsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 14 publications
3
25
1
Order By: Relevance
“…Th e pollen morphology of Declieuxia fruticosa was described by Piesschaert et al (2000) using an SEM, and these authors reported similar results to those of the present study; they also observed a "complex reticulum" in this species. Th is type of ornamentation is very similar to the bireticulate pattern described by Punt et al (2007) as a reticulum composed of two layers (a suprareticulum sustained by a microreticulate tectum).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Th e pollen morphology of Declieuxia fruticosa was described by Piesschaert et al (2000) using an SEM, and these authors reported similar results to those of the present study; they also observed a "complex reticulum" in this species. Th is type of ornamentation is very similar to the bireticulate pattern described by Punt et al (2007) as a reticulum composed of two layers (a suprareticulum sustained by a microreticulate tectum).…”
Section: Discussionsupporting
confidence: 81%
“…Among the heterostylous species studied, Declieuxia fruticosa and Leptoscela ruelioides had pollen grains of the two morpho-fl oral types analyzed, and the data presented here corroborates information in the literature concerning heterostyly in the family; the pollen grains from the brevistylous (thrum) morpho-fl oral type had larger diameters (Ganders 1979;Jung-Mendaçolli & Melhem 1995;Dessein et al 2000;Piesschaert et al 2000;Melhem et al 2003). Th ere were no diff erences between the specimens investigated in terms of aperture types or exine ornamentation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations